What Makes Cities More Productive? Evidence from 5 OECD Countries on the Role of Urban Governance - Rudiger Ahrend; Emily Farchy; Ioannis Kaplanis; Alexander C. Lembcke (Verein für Socialpolitik, Ausschuss für Wirtschaftssysteme und Institutionenökonomik, 2016)
In estimating agglomeration benefits across five OECD countries, this paper represents the first empirical analysis that contrasts cross-country evidence on agglomeration benefits with the productivity impact of metropolitan governance structures, while taking into account the potential sorting of individuals across cities. The comparability of results in a multi-country setting is supported through the use of a new internationally-harmonised definition of cities based on economic linkages rather than administrative boundaries. The analysis finds that cities with fragmented governance structures tend to have lower levels of productivity. The estimated elasticity for an increase in the number of local jurisdiction is 0.06, which is halved by the existence of a metropolitan governance body. The effect is sizeable, as the analysis confirms the result in the literature that city productivity increases with city size with an elasticity in the range of 0.02 to 0.05.
Keywords: R12; R23; R50; H73; 330; Cities; productivity; governance; agglomeration economies